2020
DOI: 10.15403/jgld-2546
|View full text |Cite
|
Sign up to set email alerts
|

HLA Alleles and KIR Genes in Romanian Patients with Chronic Hepatitis C

Abstract: Background and Aims: The role of natural killer (NK) cells in the defense against hepatitis C virus (HCV) infection involve both innate and adaptive immunity. NK cells express a large panel of inhibitory and activating receptors who bind human leukocyte antigen (HLA) class I receptors. Killer cell immunoglobulin-like receptors (KIRs) are the most polymorphic of these receptors being encoded by genes distributed differently in unrelated individuals. The aim of this study was to look at the immune response in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…HLA-C has been widely studied for its pivotal role in the immune cellular response to viral infections. Previously published studies linked specific HLA-C variants to HPV-related cervical disease [ 27 ] to patients chronically infected by HCV [ 28 ] and by HBV [ 29 ]. The focus of this work was to determine whether there was an association between HLA-C variants’ stability and HIV-1 infection control.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-C has been widely studied for its pivotal role in the immune cellular response to viral infections. Previously published studies linked specific HLA-C variants to HPV-related cervical disease [ 27 ] to patients chronically infected by HCV [ 28 ] and by HBV [ 29 ]. The focus of this work was to determine whether there was an association between HLA-C variants’ stability and HIV-1 infection control.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that KIR2DL3 in combination with HLA-C1 or C1C1 contributes to failure of the spontaneous clearance of HCV when the effect of IL28B is considered [23]. This observation was confirmed by others [24,25]. Several studies also linked KIR2DL3 with the spontaneous resolution of HCV infection [26].…”
Section: Trydzenskaya Et Al Was the First To Define A Role For Kirs I...mentioning
confidence: 82%
“…Additional HLA typing and statistical inference of HLA alleles can refine the SNP association signals to specific HLA alleles, reflecting specific molecular functions and pathways. Such a strategy was successfully implemented for infectious diseases such as HIV, HPV, Dengue, and Ebola ( Lin et al, 2003 ; Wang et al, 2011 ; Nishida et al, 2016 ; Adebamowo and Adeyemo, 2019 ; Chen et al, 2019 ; Ekenberg et al, 2019 ; Butler-Laporte et al, 2020 ; Chaisri et al, 2020 ; Huang et al, 2020 ; Ursu et al, 2020 ; Yengo et al, 2020 ).…”
Section: The Role Of Immunogenetics In Infectious Diseasesmentioning
confidence: 99%